Minimizing Enterostomy Complication in Neonates, Lessons Learnt from Three European Tertiary Centres - Riccardo Coletta; Andrea Zulli; Kathryn O'Shea; Elisa Mussi; Adrian Bianchi; Antonino Morabito (MDPI AG, 2022)
Introduction. Stoma formation in neonates is often a life-saving procedure across a variety of conditions but is still associated with significant morbidity. Tube stoma technique was originally described for short bowel patients, but in selected cases of neonates this approach could prevent the incidence of stoma-related complications. The aim of the study was to evaluate the safety and utility of tube stomas as an alternative to conventional enterostomy in the neonatal population. Material and Methods. A retrospective multicentre analysis of neonates undergoing emergency laparotomy and tube stoma formation between 2005 and 2017 was performed. Tube stoma complications were analysed. The investigation focused on stricture, skin lesion, enteric fistula and prolapse. Results. Thirty-seven neonates underwent tube stoma fashioning during the study period. Tube-stoma complications were limited to three patients (8.1%), with two children (5.4%) requiring additional stoma surgery during the first 30 days because of an enterocutaneous fistula, and one child (2.7%) for bowel stenosis. Conclusions. In select neonates, such as those with proximal enteric stomas, the tube stoma avoids some of the commonly encountered complications (prolapse, skin excoriation). Further prospective studies are needed to validate these findings in order for us to recommend this technique as superior.